General Properties of Propolis and its Usage in Ruminants - Özdemir, VF; Yanar, M; KOÇYİĞİT, Rıdvan (Journal of the Hellenic Veterinary Medical Society, 2022)
Propolis is a product with many benefits, honey bees produce propolis by mixing the resin substances they collect from the bark, leaves, and plant secretions of trees with honey, wax, pollen, and their salivary enzymes. They use this product for several purposes including protecting bee larvae, honey stores, and honeycombs from infections, repairing damaged areas, covering holes and cracks in the hive. It was also used in folk medicine with its antimicrobial and healing effects since ancient times. Beside these properties, with the advancements in science, various other properties of propolis like immunomodulatory, anti-inflammatory, antitumor, antioxidant, anticarcinogenic, antiprotozoal, antiviral, antiulcer, local anesthetic, cytotoxic, and many more were also discovered. When it was discovered that antibiotics create residues in foods and cause resistance in some microorganisms, the use of antibiotics in farm animals has been restricted in many countries. This led to an increase in the demand for organic products in the public and drove scientists to search for new natural alternative feed additives that can show similar effects with antibiotics in order to prevent economic losses caused by the restriction. In this study, it was aimed to discuss the effects of propolis in ruminants as a feed additive and its usability as a natural alternative to antibiotics by analyzing studies on the field.